Health Anxiety and Its Relationship with Academic Performance and Learning Styles among Nursing Students during COVID-19 Pandemic - Hossein Namdar Areshtanab; Mina Hosseinzadeh; Hossein Ebrahimi; Mohammad Arshadi Bostanabad; Nazila Sepehrnia (Journal of Caring Sciences)
Introduction: This study aimed to investigate health anxiety and its relationships with academic performance and learning styles among nursing students during the COVID-19 pandemic. Methods: A cross-sectional design was employed, involving 365 participants selected through stratified random sampling in Iran in 2021. Data were collected using Health Anxiety Inventory, Visual, Aural, Reading/Writing, and Kinesthetic Learning Styles Questionnaire and students’ self-reported grade point average (GPA). Data were analyzed using descriptive and inferential statistics (independent samples t-test, one-way ANOVA, Pearson correlation coefficient and chi-square test) by SPSS version 13. Results: The mean (SD) health anxiety score among nursing students was 24.33(9.79) on a range of 0-54; and the mean (SD) of GPA was 15.60 (1.51) on a range of 0-20. The majority of students (85.8%) had a unimodal learning style, with the dominant pattern being kinetic-motor (39.7%). The study found a negative correlation between health anxiety and academic performance (r=-0.19, P≤0.05). However, no significant association was identified between health anxiety and learning style (r=-0.27, P=0.42). The analysis of health anxiety among participants indicated notable differences based on demographic factors such as sex, interest in nursing, and education level (P<0.001). Conclusion: This study revealed a moderate level of health anxiety among Iranian nursing students during the COVID-19 pandemic and identified a significant negative correlation between health anxiety and academic performance. These findings underscore the need for interventions targeting health anxiety to potentially improve academic outcomes for nursing students, as reducing anxiety levels can enhance focus, learning capacity, and overall academic performance.